HUBUNGAN DEPRESI MATERNAL DENGAN FUNGSI KOGNISI ANAK USIA 7 – 14 TAHUN - Ika Saptarini; Anissa Rizkianti; Prisca Petty Arfines; Suparmi Suparmi (Puslitbang Upaya Kesehatan Masyarakat, 2020)
Abstract Background: Investing in early childhood growth and development is a strategy for preparing a better future generation. Ensuring maternal mental health, including maternal depression, is a significant effort to achieve responsive care. Objective: This study aims to analyse the association between maternal depression and cognitive function of children aged 7 – 14 years at two points, in 2007/2008 and 2014/2015. Methods: This study used IFLS-4 and IFLS-5 data. The unit of analysis were children aged 7 – 14 years and mothers who lived in the same household. Children's cognitive function was measured using the Raven method, while maternal depression was measured using CESD-10. The analysis was performed using linear regression. Results: From the IFLS-4 data, there was a significant association between maternal depression and cognitive function of children aged 7 – 14 years. Children aged 7 – 14 years with mothers with depression have a risk of having cognitive function 0.1 lower which measure with Z-score (SE: 0.05) than children with mothers without depression. However, in IFLS-5, there was no significant association between maternal depression and cognitive function. Conclusion: There were different results regarding the association between maternal depression and cognitive function of children aged 7 – 14 at the two points observed. Further studies need to be done to analyse the causality between maternal depression and cognitive function in children. Keywords: cognitive function, maternal depression. CESD-10, the raven test Abstrak Latar belakang: Investasi pada tumbuh kembang anak usia dini merupakan strategi menyiapkan generasi penerus bangsa yang lebih baik. Menjaga kesehatan mental ibu termasuk depresi maternal merupakan upaya untuk mencapai pengasuhan yang responsif. Tujuan: Studi ini bertujuan untuk melihat hubungan antara depresi maternal dengan fungsi kognisi anak usia 7 – 14 tahun pada dua titik yaitu tahun 2007/2008 dan tahun 2014/2015. Metode: Studi ini menggunakan data IFLS-4 dan IFLS-5. Unit analisis adalah anak usia 7 – 14 tahun dan ibu yang tinggal dalam satu rumah. Kognisi anak diukur menggunakan metode Raven, sedangkan depresi maternal diukur menggunakan CESD-10. Analisis dilakukan menggunakan regresi linear. Hasil: Dari data IFLS-4 didapatkan hubungan yang bermakna antara depresi maternal dan fungsi kognisi anak usia 7 – 14 tahun. Anak usia 7 – 14 tahun dengan ibu mengalami depresi berisiko memiliki fungsi kognisi 0,1 lebih rendah yang dinilai menggunakan Z-score (SE:0,05) dibanding anak dengan ibu tanpa depresi. Namun pada IFLS-5 tidak terdapat hubungan yang bermakna antara depresi maternal dan fungsi kognisi. Kesimpulan: Terdapat hasil yang berbeda terkait hubungan depresi maternal dan fungsi kognisi anak usia 7 – 14 tahun pada dua titik tahun yang diamati. Perlu dilakukan studi lanjutan untuk melihat kausalitas antara depresi maternal dan fungsi kognisi anak. Kata kunci: fungsi kognisi, depresi maternal, CESD-10, tes raven